Correlation between Patient's Age and Advanced Response Time with Outcome of Cardio Pulmonary Resuscitation in Cardiac Arrest Patient - Setiarini, Debie; Kriswidyatomo, Prihatma; Sari, Gadis Meinar (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: This study is conducted to determine the correlation between patient's age and advanced response time with the outcome of Cardio Pulmonary Resuscitation in cardiac arrest patients. Methods: This was an analytic observational cross-sectional study, evaluating correlation between patient's age and advanced response time with the outcome of Cardio Pulmonary Resuscitation in cardiac arrest patients. This study used the primary data from Cardio Pulmonary Resuscitation sheets from February to August 2018 at Dr. Soetomo General Hospital, Surabaya. The data were analysed with Chi Square and Contingency Coefficient using SPSS version 22.0. Results: The results showed that 84.6% cardiac arrest patients who experience ROSC are over 40 years old, and 92.3% cardiac arrest patients who experience ROSC have advanced response time â‰¤ 5 minutes. After being tested using Chi Square, patient's age was not statistically influencing the outcome in cardiac arrest patients (p = 0.507), but advanced response time was statistically influencing the outcome in cardiac arrest patients (p = 0.001). Conclusion: There was no statistically influence of patient's age towards the outcome in cardiac arrest patients, but there was a significant influence of advance response time towards the outcome in cardiac arrest patients.